Post-Pandemic Inflationary Pressure and Global Commodity Price Shocks in Indonesia: An ARDL Estimation - Zainab Aslam; Saba Ansari (Budi Luhur Journal of Strategic & Global Studies, 2026)
Abstract: The volatility of world commodity prices has emerged as a major force of macroeconomic stability in the developing economies, especially those with food and energy as the main components in the spending of households. Being among the biggest economies that largely rely on commodity imports, Indonesia is extremely vulnerable to price shocks caused by externalities, particularly in the aftermath of the pandemic when inflationary pressures were at their height. In this analysis, the focus is on the transmission of global food and crude oil price shocks into the domestic inflation processes in Indonesia. The study used the annual data from 1988 to 2023, from the World Bank World Development Indicators (WDI) and the World Bank Pink Sheet to explain inflationary behaviour. The Autoregressive Distributed Lag (ARDL) model using the bounds test has been employed to check the long-run as well as short-run effects. The findings indicate that global oil price shocks have a major impact on increasing inflation in the short run, but food prices and exchange rate depreciation have a lesser but positive impact. Interest rates and growth of GDP have minimal short-run effects, and this indicates that the current episode of inflation in Indonesia is mainly caused by external cost-push and not by domestic demand. In the long run, the global food process shows a deflationary effect on inflation. The implication of these results is the necessity of better measures of food and energy price stabilization, exchange-rate management, diversification of imports, and enhancement of domestic productivity. The study adds a novel piece of evidence regarding the inflation behaviour in the post-pandemic period in Indonesia and the significance of resilience-oriented policy in dealing with the risks of inflation caused by commodities. Abstrak: Volatilitas harga komoditas dunia telah muncul sebagaikekuatan utama stabilitas makroekonomi di negara-negara berkembang, terutama yang memiliki makanan dan energi sebagai komponen utama dalam pengeluaran rumah tangga. Sebagai salah satu negara dengan perekonomian terbesar yang sangat  impor komoditas, Indonesia sangat rentan terhadap guncangan harga yang disebabkan oleh eksternalitas, terutama setelah pandemi ketika tekanan inflasi berada pada puncaknya. Dalam analisis ini, fokusnya adalah pada transmisi guncangan harga pangan global dan minyak mentah ke dalam proses inflasi domestik di Indonesia. Studi ini menggunakan data tahunan dari tahun 1988 hingga 2023, dari World Bank World Development Indicators (WDI) dan World Bank Pink Sheet untuk menjelaskan perilaku inflasi. ModelAutoregressive Distributed Lag (ARDL) menggunakan uji batas telah digunakan untuk memeriksa efek jangka panjang maupun jangka pendek. Temuan menunjukkan bahwa guncangan harga minyak global berdampak besar pada peningkatan inflasi dalam jangka pendek, tetapi harga pangan dan depresiasi nilai tukar memiliki dampak yang lebih kecil namun positif. Suku bunga dan pertumbuhan PDB memiliki dampak minimal dalam jangka pendek, dan ini menunjukkan bahwa episode inflasi saat ini di Indonesia terutama disebabkan oleh dorongan biaya eksternal, bukan oleh permintaan domestik. Dalam jangka panjang, proses pangan global menunjukkan efek deflasi terhadap inflasi. Implikasi dari hasil ini adalah perlunya langkah-langkah yang lebih baik untuk stabilisasi harga pangan dan energi, pengelolaan nilai tukar, diversifikasi impor, dan peningkatan produktivitas domestik. Studi ini menambahkan bukti baru mengenai perilaku inflasi pada periode pasca-pandemi di Indonesia dan pentingnya kebijakan berorientasi ketahanan dalam menghadapi risiko inflasi yang disebabkan oleh komoditas.